2021
DOI: 10.37268/mjphm/vol.21/no.3/art.1197
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude Towards Geriatric Health and the Associated Factors Among Medical Students of International Islamic University Malaysia

Abstract: Comprehensive care towards geriatric health can be sustained by having good knowledge and attitude among the providers. Hence, this research aims to measure the knowledge and attitude of the final year medical students towards geriatric health and determine the associated factors. A cross-sectional study was conducted among the students using structured questionnaires of Geriatric-Attitude-Scale and Palmore-Facts-on-Aging-Quiz was used. Data was analysed using Mann Whitney U test, Chi square test and Spearman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…This is lower than the 3.37 out of 5 scores among medical and nursing students in Saudi Arabia [ 6 ]. A study conducted in Malaysia that used the Geriatric Attitude Scale also concluded that its sample had moderate knowledge and attitudes regarding elderly care [ 7 ]. In 2009, two published studies explored the attitudes towards the elderly among medical students and junior doctors in Singapore.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is lower than the 3.37 out of 5 scores among medical and nursing students in Saudi Arabia [ 6 ]. A study conducted in Malaysia that used the Geriatric Attitude Scale also concluded that its sample had moderate knowledge and attitudes regarding elderly care [ 7 ]. In 2009, two published studies explored the attitudes towards the elderly among medical students and junior doctors in Singapore.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in Malaysia also found medical students to have moderate knowledge about the elderly. However, it showed a statistically significant association between knowledge and attitude towards the elderly and the presence of grandparents, area of residence, and number of siblings [ 7 ].…”
Section: Introductionmentioning
confidence: 99%